Roman and medieval coins found in Scotland, 1996-2000 - Bateson, J D; Holmes, N M McQ (Proceedings of the Society of Antiquaries of Scotland, 2004)
This survey covers some 350 sites which have yielded Roman or later coin finds in the five years since the beginning of 1996.